Has Deep Brain Stimulation Changed the Very Long‐Term Outcome of Parkinson's Disease? A Controlled Longitudinal Study. Issue 7 (21st September 2020) - Mahlknecht, Philipp; Peball, Marina; Mair, Katherina; Werkmann, Mario; Nocker, Michael; Wolf, Elisabeth; Eisner, Wilhelm; Bajaj, Sweta; Quirbach, Sebastian; Peralta, Cecilia; Eschlböck, Sabine; Wenning, Gregor K.; et al.
ABSTRACT: Background: The long‐term impact of deep brain stimulation (DBS) on Parkinson's disease (PD) is difficult to assess and has not yet been rigorously evaluated in comparison to its natural history. Objective: Comparison of key disability milestones (recurrent falls, psychosis, dementia, and institutionalization) and death in patients with PD with versus without DBS. Methods: We collected retrospective information from clinical notes of patients with PD at our center that were implanted with subthalamic DBS >8 years ago (1999–2010) and a control group of PD patients without DBS similar in age at onset, age at baseline, sex distribution, and number of comorbidities at baseline (extracted from a registry study performed in 2004). Cox regression models were used to calculate hazard ratios, adjusted for potential baseline confounding variables (age, sex, disease duration, disease severity, and number of comorbidities). Results: A total of 74 DBS‐treated and 61 control patients with PD were included. For a median observational period of 14 years, patients treated with DBS were at lower risk of experiencing recurrent falls (hazard ratio = 0.57; 95% confidence interval, 0.37–0.90; P = 0.015) and psychosis (hazard ratio = 0.26; 95% confidence interval, 0.12–0.59; P = 0.001) compared with control patients. There was no significant difference in risk for dementia, institutionalization, or death. Disease progression as assessed by Hoehn and Yahr scores was not slower in DBS‐treated patients. Conclusions: Treatment with chronic subthalamic DBS was associated with lower risk for recurrent falls and psychotic symptoms, effects that may be mediated through improved motor symptom control and reduction in dopaminergic therapies, respectively. There was no evidence for DBS effects on underlying disease progression.